Epidermolytic Acanthoma Mimicking Condyloma: A Case Report - Amandine Dupont; Hélène Marescassier; Gürkan Kaya (MDPI AG, 2019)
Epidermolytic acanthoma is a rare benign tumor that appears as a solitary papule or, rarely, multiple small papules on the trunk and extremities, or on genitalia. They are generally asymptomatic, although they can be pruritic. The clinical presentation is often misleading, and the lesions are often misdiagnosed histologically and frequently confused with condyloma acuminatum. Here, we report a case of an epidermolytic acanthoma on the penis of a 57-year-old male, whose final diagnosis was made after several years.